Evaluation and Design of User Interface / User Experience on the INMAX Property Website Using the Double Diamond Model - Laksono, Bagus; Sagirani, Tri; Wardhanie, Ayouvi Poerna (Jurnal Sistem Informasi Universitas Dinamika, 2021)
PT Inmaksindo Infiniti Graha is a real estate company in Surabaya and has a website, namely https://www.inmaxproperty.com. The website is used for the process of buying and renting property, users of the INMAX Property website are people who are looking for property to buy or rent. The problem is when users who want to buy property access the website there are several problems, such as inadequate information, there is a lack of filters in the search feature, no login and register features, and no agent scheduling and indent property features. From these problems, evaluation is carried out using the Heuristic Evaluation method consisting of 10 principles, namely Visibility of system status, Match between system and the real world, User control and freedom, Consistency and standards, Error prevention, Recognition rather than recall, Flexibility and efficiency of use, Aesthetic and minimalist design, help users recognize, diagnose, and recover from errors, Help and documentation. Based on the results of the evaluation, it was found that there were improvements in the indicators of Consistency and Standards, Flexibility and Efficiency of Use, and Help and Documentation. Therefore, a redesign was carried out with the Double Diamond model with the steps Discover, Define, Develop and Deliver. Based on the results of the redesign that have been evaluated, it is found that the display indicator of the KPR simulation on the principle of Consistency and Standards which was previously 1.90 (respondents disagreed) after the redesign increased to 2.73 (respondents agreed). Meanwhile, the Email Agent button is available to discuss the property on the principle of Flexibility and Efficiency of Use before redesigning the mean is 2.43 (respondents disagree) after redesign it increases to a mean of 3.03 (respondents agree). Whereas in the indicator there is a contact us feature to make it easier for users who want to ask about the desired property in the Help and Documentation principle before redesigning the mean 2.47 (respondents disagree) after redesign it increases to mean 3.30 (respondents agree). For other principles, there is no need for improvement because the respondent agrees with the existing design.